2022
DOI: 10.1111/zph.12948
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of influenza A infection and risk of transmission between pigs and farmworkers

Abstract: Interspecies transmission of influenza A virus (IAV) between pigs and people represents a threat to both animal and public health. To better understand the risks of influenza transmission at the human–animal interface, we evaluated 1) the rate of IAV detection in swine farmworkers before and after work during two human influenza seasons, 2) assessed risk factors associated with IAV detection in farmworkers and 3) characterized the genetic sequences of IAV detected in both workers and pigs. Of 58 workers provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…In accordance with the aforementioned studies, we observed a significantly higher chance of detecting influenza by rRT-PCR in weaners compared to suckling piglets or nursery pigs, which most likely results from the mixing of piglets after weaning, either for transport or within the pens. Furthermore, the additional subsequent spread of the virus in the nursery units, due to airflow or even farm stuff [ 11 ], plays a role. The speed of infection depends on the subtypes involved [ 38 ], the extent of mixing, and the group sizes within the nursery units [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the aforementioned studies, we observed a significantly higher chance of detecting influenza by rRT-PCR in weaners compared to suckling piglets or nursery pigs, which most likely results from the mixing of piglets after weaning, either for transport or within the pens. Furthermore, the additional subsequent spread of the virus in the nursery units, due to airflow or even farm stuff [ 11 ], plays a role. The speed of infection depends on the subtypes involved [ 38 ], the extent of mixing, and the group sizes within the nursery units [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data clearly show that in farms either suspecting an endemic circulation of swIAV or an acute outbreak, the percentage of healthy swIAV-positive suckling piglets (7.2% of all samples) was higher than the percentage of diseased swIAV-positive suckling piglets (4.2% of all samples). As suckling piglets can serve as a reservoir for swIAV, the main aspects that have to be considered to reduce swIAV circulation during the suckling period include the vaccination management of sows and gilts [ 30 , 45 ] and the management of suckling piglets, to minimize transmission [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study using whole genome sequencing found that IAV samples from five workers had identical clade classification to swine-origin IAV samples from pigs on the same farm (27).…”
Section: Introductionmentioning
confidence: 99%
“…In a separate seroprevalence study evaluating farmers, meat processing workers (from pork production facilities), veterinarians with swine exposure and controls with no known contact with swine, it was found that farmers had the highest odds of swine influenza exposure (Odds Ratio [OR], 35.3; 95% CI, 7.7 – 161.8) (26). Another study using whole genome sequencing found that IAV samples from five workers had identical clade classification to swine-origin IAV samples from pigs on the same farm (27).…”
Section: Introductionmentioning
confidence: 99%